The Response of the Cipari Village Community, Garut Regency, to the DI/TII Rebellion 1949-1962 - Ghaitsa Ramdani; Ading Kusdiana; Yasmina Wikan Astri (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
This research discusses the response of the people of Cipari Village, Garut Regency, to the Darul Islam/Tentara Islam Indonesia (DI/TII) rebellion during the period 1949-1962. The main focus is the role of the Cipari Islamic Boarding School led by K.H. Yusuf Tauziri in countering DI/TII ideological extremism while maintaining moderate Islamic values and loyalty to the Unitary State of the Republic of Indonesia (NKRI). This research uses a historical method that includes heuristics, criticism, interpretation, and historiography. Data were collected through interviews, archival documents, and literature review. The results revealed the importance of the role of pesantren as agents of socio-political change in Indonesia. As a traditional institution, pesantren not only maintain religious values, but also become a moral and social fortress capable of facing the threat of ideological extremism. Cipari Islamic boarding school shows an important contribution in maintaining national integration and fighting separatist movements that threaten the integrity of the nation. K.H. Yusuf Tauziri played a strategic role by leading the Darussalam laskar and the people of Cipari Village to face more than 50 attacks by DI/TII troops. His approach to rejecting DI/TII extremism by emphasizing internal reform, preaching, and defensive resistance, made the Cipari Islamic Boarding School a symbol of strong ideological and physical resistance.